2023
DOI: 10.1038/s41598-023-35970-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of TLR2 and aging on the humoral immune response to Staphylococcus aureus bacteremia in mice

Abstract: Aging alters immunoglobulin production, affecting the humoral immune response. Toll-like receptor 2 (TLR2) recognizes Staphylococcus aureus (S. aureus) which causes bacteremia with high mortality in the elderly. To understand how TLR2 and aging affect the humoral immune response in bacteremia, four groups of mice (wild type-young, wild type-old, TLR2−/−-young, and TLR2−/−-old) were used to analyze immunoglobulin levels in healthy conditions as well as 10 days after intravenous injection with S. aureus. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
(67 reference statements)
5
1
0
Order By: Relevance
“…In line with previous studies of Staphylococcus infection in mice [25] and elderly humans [26], we found an increase in the older mice in all types of circulating IgG and subtypes. Serum IgG subclass levels were shown to vary with inflammation and age, although it is not constant, as described in several studies [25,27,28]. In this study, IgG1 levels mainly increased following the immune challenge, like our previous study on the Staphylococcus challenge in mice [25].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous studies of Staphylococcus infection in mice [25] and elderly humans [26], we found an increase in the older mice in all types of circulating IgG and subtypes. Serum IgG subclass levels were shown to vary with inflammation and age, although it is not constant, as described in several studies [25,27,28]. In this study, IgG1 levels mainly increased following the immune challenge, like our previous study on the Staphylococcus challenge in mice [25].…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that antigen-specific antibody response is predominantly decreased in older people [24]. However, consistent with our previous study in systemic bacteremia, where age did not alter the antigen-specific IgG [25], we show no differences between young and adult mice in mBSA-specific IgG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, our recent study, employing aging and TLR-2 deficient mice, disclosed that increased age stood out as the primary contributor to heightened mortality rates and changes in spleen weight ( Hu et al, 2023 ). Surprisingly, the severity of septic arthritis remained unaltered by aging, even though aged mice demonstrated an insufficient antibody response to S. aureus infection ( Gupta et al, 2023 ).…”
Section: To Study the Role Of Host Factors In Septic Arthritismentioning
confidence: 99%